Impact of the Stringency of Attendance Policies on Class Attendance/Participation and Course Grades - Liugen Zhu (Journal of the Scholarship of Teaching and Learning, 2019)
The purpose of this preliminary study was to investigate the impact of three diverse attendance and participation policies in face-to-face and online courses and the effect on students’ final grades in each course. We examined nine different undergraduate courses taught between Fall 2010 and Spring 2015. The results suggest that a more stringent attendance policy significantly impacts student attendance, absences were negatively correlated with course grades, and that course delivery methods were not predictive of either attendance/participation or course grades.  Additional research is needed to determine what other factors might influence attendance and participation and correlation to course grades.